Antithyroid antibody (TPO-Ab) Status in Type 2 Diabetic Patients (KYAMC Journal, 2023)
Background: Presence of thyroid peroxidase antibody (TPO-Ab) in type 2 diabetic patients is a risk factor for future development of thyroid dysfunction.Objective: To observe thyroid antibody status in type 2 diabetic patients.Materials & Methods: This cross sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka from July 2016 to June 2017. Total 60 subjects including  male and female, age ranged from 40 to 60 years were included in this study, among them 30 were non-diabetic subjects and 30 were type 2 diabetic patients.Results: In this study, mean serum TPO-Ab level was significantly (